Isharat al-nass in the Qur'an : an analysis of its role in the Qur'anic interpretation - Ahmad, Usman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Fuqaha' (legal experts in Islamic Law) and mufassirun (commentators of the Qur'an) have applied several well-defined as well as undefined methodologies to either interpret the Qur'an, the first source of Islamic law, or to derive certain particular import/s from the word/s of Qur'anic ayat. One such not so defined way to derive message from the Qur'anic word/s is deliberation over isharat al-naṣṣ(implied meaning of revealed words). Isharat al-Naṣṣ may be defined as far-fetched indication of certain meaning in a particular statement of the Qur'an. This, as a natural corollary, has been used and misused. Mu'tazilah, Asha'irah, and sufiya' are the most prominent in employing isharat al-naṣṣ for their respective purposes. It is claimed that deviation in the interpretation of some Qur'anic injunctions is consequent upon manipulation of the revealed words in the name of isharat al-nass. This research focused on (1) reasoning on isharat al-naṣṣas a delicate tool to interpret the Qur'an, (2), role of isharat al-naṣṣ in explaining in apparent contradiction among Qur'anic precepts and (3) pitfalls in the reasoning on isharat al-naṣṣ. Fiqhi ijtihad by different fuqaha' leads, at times, to differences in the interpretation of the Qur'an. The main reason for this is different ways of reasoning on isharat al-naṣṣ. The main thrust of this thesis is on how proper reasoning on ishārat al-naṣṣ may be used as an authentic method to interpret Qur'anic ayat, on the one hand, and to remove apparent contradiction available in the revealed words, on the other. The methodology applied in this thesis is mainly analytical with critical overtones.